Quality of Life among Ostomates Attending at a Cancer Hospital, Chitwan, Nepal - Neupane, Laxmi; Thulung, Bedantakala (Journal of Chitwan Medical College, 2019)
Background: Stoma is a global public health problem. Stoma can be temporary or permanent and creates multiple difficulties in terms of quality of life (QoL). So the QoL of ostomates needs to be regularly assessed. The objective of the study was to find out the Quality of life among ostomates attending outpatient clinics at a Cancer Hospital, Chitwan. Methods: A descriptive cross sectional study was conducted among 138 ostomates. Consecutive sampling technique was used by face to face interview method using standard tool “City of Hope Quality of Life Questionnaire for a patients with an ostomy”. Data were analyzed by using descriptive and inferential statistics. Results: The mean QoL of the respondents was 5.03±0.75. More than half (52.9%) of the respondents had lower QoL. Statistical significant association was found between QoL of the respondents and recent involvement in occupation (p<0.001), duration of having stoma (p=0.049) and stoma related complications (p=0.014). There is a positive correlation between overall QoL of the respondents and QoL in physical domain (r=0.632, p<0.001), psychological domain (r=0.723, p<0.001), social domain (ρ =0.809, p<0.001) and spiritual domain (r=0.581, p=0.001) respectively. Conclusions: It is concluded that more than half of respondents had lower QoL. Here, stoma affects all domains of QoL of ostomates. Qualitative study explores all aspect of life more effectively. Counseling must be directed to continue job, adjustment to changed life style and prevention of complication.